Human Resources Development, Using a Humanism Sufistik Approach - Ahmad Zarkasyi (Qolamuna : Jurnal Studi Islam, 2019)
This article offers the concept of human resources development by using a humanism sufisktik approach. Humanism focuses award and the development potential of human nature, so manifest psychologically stable growth to the level of self – actualization. Sufi enchance the role of moral and psychological motivated by value al fadilah kamal an-nafs based on Islam. Sufistik humanism implies that the translation of humanizing meaning it must alwasy be related to theological moral manners. By this approach, the expected moslem human resources are able to competitate until become the leader who are not only in ASEAN but also in the scale of international. Keyword: Human Resources Development, Humanism, Sufistik